2022
DOI: 10.1002/pc.27171
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the tensile properties of PA6/CNT nanocomposite in selective laser sintering process

Abstract: The aim of present study is to enhance the tensile strength, elongation at break and tensile modulus of polyamide 6/carbon nanotube (PA6/CNT) nanocomposite prepared by selective laser sintering. For this purpose, the optimal values of laser power, scanning speed and CNT content were estimated to enhance the tensile properties of PA6/CNT nanocomposite by using the response surface methodology and desirability function. The microstructure of specimens

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…Agglomeration of the CNTs led to poor distribution of the nanoparticles and thus the degradation of weld strength. The enhancement of the TS of polyamide composites by addition of CNTs was also found by Taher et al, [ 14 ] Qi et al, [ 17 ] Vidakis et al, [ 45 ] and Bai et al [ 46 ]…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…Agglomeration of the CNTs led to poor distribution of the nanoparticles and thus the degradation of weld strength. The enhancement of the TS of polyamide composites by addition of CNTs was also found by Taher et al, [ 14 ] Qi et al, [ 17 ] Vidakis et al, [ 45 ] and Bai et al [ 46 ]…”
Section: Resultssupporting
confidence: 62%
“…Agglomeration of the CNTs led to poor distribution of the nanoparticles and thus the degradation of weld strength. The enhancement of the TS of polyamide composites by addition of CNTs was also found by Taher et al, [14] Qi et al, [17] Vidakis et al, [45] and Bai et al [46] The significant interaction of parameters versus the impact and tensile strengths was presented by response surface plots. Based on the ANOVA results (in Table 5), it was found that the influence of the interaction of laser power and welding velocity (LP Â WV) as well as laser power and CNT content (LP Â CNT) is significant on the impact and tensile strengths.…”
Section: Analysis Of Microstructuresupporting
confidence: 58%
See 2 more Smart Citations
“…Figure 1 shows the classic confocal optical path.In the overall layout of the optical path, the briefness and practicality of the overall structure are fully considered, and the minimum number of lenses is used as much as possible to accomplish the expected goals. In the design process, Zemax software is utilized in this paper for the design of the confocal optical path [2] . The radial and axial resolution of the confocal optical imaging system is determined by the wavelength and numerical aperture.…”
Section: General Layout and Design Goalmentioning
confidence: 99%